Dead heart - Parsons, Nick (Sydney Currency Press, 1996)
"Six hundred kilometres west of Alice Springs lies Wala Wala, a tiny community of besser-brick huts adrift on the scrubby desert. An unorthodox group of white fringe dwellers minister to a floating population of tribal aborigines." "The schoolteacher's wife, Kate, has begun an affair with Tony, the good-looking but rebellious Aboriginal teacher's aide. Unknown to her, Tony has made love to her on a sacred site. When this sacrilege is discovered, Mannga and Poppy, two local elders, decide there can be only one penalty. The following morning, Tony is found dead in his bedroll." "To Ray Lorkin, the tough and pragmatic local constable, this traditional execution is murder. His determination to seek justice throws two laws into fatal and bloody conflict." "Dead Heart is adapted by Nick Parsons from his award winning stageplay. It has been screened at the international film festivals of Toronto, Hampton, Hamburg, London and Los Angeles." "The full script with stills from the film is presented here with an introduction by David Stratton."--Book jacket.
Keywords: Dead heart (Motion picture) .